1974
DOI: 10.1002/bjs.1800610406
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the pathogenesis of peritoneal adhesions: a light and electron microscopical study

Abstract: 1, Observations have been made by light and electron microscopy of the development of peritoneal adhesions in lhe rat following abdominal surgery.2. Essentially the changes which occurred were those which are seen in healing by fibrosis, except that in many areas of adhesions numerous eosinophils were observed by electron microscopy. In areas where eosinophils were numerous little profijeration of fibroblasts was seen. Conversely in sites where fibroplasia and collagen formation were well advanced no eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
13

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(84 citation statements)
references
References 18 publications
2
69
0
13
Order By: Relevance
“…Our study found that collagen was most prominent on Day 7, which is consistent with findings of other studies. Collagen synthesis, which reached its highest level between the fifth and seventh postoperative days (Haney and Doty, 1994;van Hinsbergh et al, 1990), allowed for adhesion maturation (Hickey, 2001;Milligan and Raftery, 1974). After 1 week, the fibrosis, which was vital to adhesion formation at this time, was less obvious in the NOCC group.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that collagen was most prominent on Day 7, which is consistent with findings of other studies. Collagen synthesis, which reached its highest level between the fifth and seventh postoperative days (Haney and Doty, 1994;van Hinsbergh et al, 1990), allowed for adhesion maturation (Hickey, 2001;Milligan and Raftery, 1974). After 1 week, the fibrosis, which was vital to adhesion formation at this time, was less obvious in the NOCC group.…”
Section: Discussionmentioning
confidence: 99%
“…5-10. günlerde kollajen birikimi olur ve fibroblastlar adezyonlar içinde organize olmaya başlarlar. Yaralanmadan 1-2 ay sonra ise kollajen fibriller organize olurlar ve böylece adezyon, fibroz band yapısına olgunlaşır [13,22,23]. Böylece, adezyon oluşum mekanizması tamamlanır (Şekil 5).…”
Section: Cerrahi̇ Adezyon Oluşumunun Sebepleri̇unclassified
“…Mast cells have been implicated in the aethiopathology of post-operative peritoneal adhesions as well as eosinophils, macrophages, and neutrophils by influencing some of the fibroblasts and myofibroblasts biochemical-functional properties. In adhesion formation process it is possible to identify a surgical trauma in conjunction with ischemia with infection that results in an acute fibroproliferative inflammatory response [4]. Post-operative adhesion may represent the final results of an exaggerated repair mechanism.…”
Section: Introductionmentioning
confidence: 99%